"COMPULSORY PILOTAGE" a system in need of reform - Manjezi, Monwabisi (Centre for Law and Society, 2026)
Following the grounding of John Fredriksen's 147 200-dwt tanker the Sea Empress earlier in 1996, for which pilot error was blamed, has again revived the debate about the liability of pilots performing a pilotage act under compulsory pilotage 1. The independent tanker owner's association, based in Oslo representing the interests of tanker and shipowners is putting pressure on the pilots to guide ships they are navigating safely into ports. They are lobbying for the removal of the legal immunity enjoyed by pilots and make them legally liable for collisions and grounding of vessels under their guidance during compulsory pilotage. The shipowners are putting pressure on harbour authorities to be given the power to choose which pilots to use in a similar way as they appoint masters. At present under the compulsory pilotage system shipowners accept a pilot without knowledge of his record and often with no option. The shipowners argue that the past performance and training of a pilot should be public knowledge and available to the owner in advance.